Effectiveness of probiotics on the duration of illness in healthy children and adults who develop common acute respiratory infectious conditions: a systematic review and meta-analysis. Issue 1 (14th July 2014) - King, Sarah; Glanville, Julie; Sanders, Mary Ellen; Fitzgerald, Anita; Varley, Danielle
<x content-type="archive" xml:space="preserve">Abstract</x> Recent systematic reviews have reported a positive, although modest, effect of probiotics in terms of preventing common cold symptoms. In this systematic review, the effect of probiotics, specifically Lactobacillus and Bifidobacterium strains, on the duration of acute respiratory infections in otherwise healthy children and adults was evaluated. To identify relevant trials, eight databases, including MEDLINE, Embase, the Cochrane Database of Systematic Reviews (CDSR), the Cochrane Central Register of Controlled Trials (CENTRAL), the Database of Abstracts of Reviews of Effects (DARE), Health Technology Assessment (HTA), Science Citation Index (SCI) and OAISTER, were searched from inception to 20 July 2012. Details regarding unpublished studies/databases were also obtained from probiotic manufacturers. Study selection, data extraction and quality assessment were carried out by two reviewers. Risk of bias was assessed using criteria adapted from those published by the Centre for Reviews and Dissemination. In this review, twenty randomised controlled trials (RCT) were included, of which twelve were considered to have a low risk of bias. Meta-analysis revealed significantly fewer numbers of days of illness per person (standardised mean difference (SMD) − 0·31 (95 % CI − 0·41, − 0·11), I2= 3 %), shorter illness episodes by almost a day (weighted mean difference − 0·77 (95 % CI − 1·50, − 0·04), I2= 80 %) (without an increase in the number of illness episodes), and fewer numbers of days absent from day care/school/work (SMD − 0·17 (95 % CI − 0·31, − 0·03), I2= 67 %) in participants who received a probiotic intervention than in those who had taken a placebo. Reasons for heterogeneity between the studies were explored in subgroup analysis, but could not be explained, suggesting that the effect sizes found may differ between the population groups. This systematic review provides evidence from a number of good-quality RCT that probiotics reduce the duration of illness in otherwise healthy children and adults.